Empire : what ruling the world did to the British - Paxman, Jeremy (London : Viking, 2011)
The influence of the British Empire is everywhere, from the very existence of the United Kingdom to the ethnic composition of our cities. This title offers an analysis that goes to the heart of empire. It deals with the tragedy and comedy of Empire and reveals its profound effect on our nation and ourselves.
Includes bibliographical references and index.
Keywords: Great Britain -- Colonies -- History; Great Britain -- Colonies -- Administration -- History; Great Britain -- Colonies -- Ethnic relations